Performance Analysis of Optimized Screen-Printed Electrodes for Electrochemical Sensing - Ab Rahim, Rosminazuin; Roslan, Nurul Amira Farhana; Md Ralib, Aliza Aini; Za'bah, Nor Farahidah; Nordin, Anis Nurashikin; Bashri, Mohd Saiful Riza; Suhaimi, Muhammad Irsyad; Samsudin, Zambri; Lim, Lai Ming; Sugandi, Gandi (International Journal of Integrated Engineering, 2022)
The screen-printed electrode (SPE) sensor is widely employed in food analysis, environmental health monitoring, disease detection, toxin detection and other applications. As it is crucial for the SPE sensor to have an outstanding performance, this study examined the effects of manipulating the working electrode (WE) area, gap spacing between electrodes, and counter electrode (CE) width on the performance of an SPE sensor. Finite element simulation on various geometrical dimensions was done prior to screen-printed electrode SPE sensors fabrication at Jabil Circuits Sdn Bhd. The electrodes performance is measured through cyclic voltammetry (CV) using a potentiostat at an optimum scan rate of 0.01 V/s and a voltammetry potential window range of -0.2 to 0.8 V in 0.01 M Phosphate Buffered Saline (PBS) solution. It is discovered that adjusting the WE area and the gap separation between the electrodes had the most impact on sensor performance compared to varying the CE width. In both simulation and CV measurement, a WE with a radius of 0.9 mm, an area of 2.54 mm2, and a gap spacing of 0.7 mm has shown the highest current density which is translated as the highest sensitivity. Further CV measurement in nicotine sensing application has proven that the SPE sensor can effectively detect the nicotine oxidation indicating its promising potential as a biosensor. Combination of optimum SPE dimension together with suitable electrode modification process serves as the basis for an effective and sensitive SPE sensor for various biosensing applications.